Determining initial psychometric properties of parenting sense of competence scale in the context of Bangladesh - Ferdowshi, Nafiza; Sultana, Niger (Dhaka University Journal of Biological Sciences, 2019)
The purposes of the present study were to translate the Parenting Sense of Competence (PSOC) scale and to determine its initial psychometric properties. Three hundred mothers were selected as participants from Dhaka city who have children aged 6 to 10 years. Collected data were analyzed to determine psychometrics by using Cronbach alpha, Spearman-Brown’s split-half and exploratory factor analysis. Results showed that internal consistencies were: Cronbach α = 0.663 and split-half reliability r = 0.636. As both internal consistencies value were quite similar that would make PSOC scale’s reliability more supportive. Initially validity was conducted on pilot basis by measuring content validity and construct validity (r = 0.628, p < 0.01). Study limitations and further implications were also discussed. Dhaka Univ. J. Biol. Sci. 28(2): 211-218, 2019 (July)